Labour Laws in the Garment Sector of Bangladesh: a Workers’ View - Mohammad Shahidul Islam; Md. Abdur Rakib (Yuridika, 2019)
The labour laws of Bangladesh ensure the rights of the labourers. The objective of this study is to explore the labour law practices in the ready-made garment sector of Bangladesh. The survey is used to collect data, percentile and descriptive statistics are used to interpret the results. Most of the cases’ employment conditions-maternity benefit, working hours, paid leave, sufficient wage- are at a satisfactory level but improvements are sometimes needed concerning trade unions, profit participation and health issues. The garment sector should implement the labour laws for the welfare of the labourers and the situation needs monitoring by the government. The purpose of the study ‘Labour Laws in the Garment Sector of Bangladesh: A Workers’ View’ by Mohammad Shahidul Islam and Abdur Rakib (Bangladesh) is to investigate labour law practices in the garment sector in Bangladesh. With a questionnaire, survey data was collected from companies and workers. The researchers concluded that in many cases the employment law situation was in order (i.e. employment conditions, maternity allowance, working hours and leave), but that in some cases improvement is needed (i.e. trade unions, profit participation, and the health of employees).